4x−3=3x−9 .(1 point) Responses= x=5 x=7x=−2 x=−6

1 answer

To solve the equation 4x - 3 = 3x - 9, we can start by isolating the x term on one side of the equation.

Subtracting 3x from both sides, we get:
4x - 3 - 3x = 3x - 9 - 3x
x - 3 = -9

Next, we can add 3 to both sides to isolate the x term:
x - 3 + 3 = -9 + 3
x = -6

So the solution to the equation is x = -6.
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. QuestionIf you are looking at an object straight on, what type of perspective are you seeing? (1 point) Responses one-point
    1. answers icon 1 answer
  2. The number line shows the locations of points P, Q, R, and S.Which points have a distance of 5 units between them? (2 points)
    1. answers icon 1 answer
more similar questions